Developing a News Channel About Vocational Education for TIMES Indonesia - Alfian, M. Ade Nur; Cahyani, Hilda Cahyani; Anyassari, Nugrahaningtyas Fatma (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aimed to develop a news channel entitled “English” by helping to create news articles that focus on the theme of Vocational Education with the scope of institutions or campuses in the Malang Area as many as 20 news articles or 8.267 words. This research was conducted based on problems in the leading mass media “TIMES Indonesia” which has an “English” channel. It is known that they only upload news articles on the “English” channel one to two times a day. The problem is emphasized by a statement from one of the English Editor team stating that basically, they compile English news articles with the majority focusing on four themes namely entertainment, lifestyle, tourism, and culinary. From the competition among other online-based mass media, TIMES Indonesia is not very prominent in terms of uploading English news articles. The researcher applied the Design and Development Research model by Richey and Klein (2014) by adapting five stages, namely analysis, design, development, implementation, and evaluation. Data collection conducted by the researcher was observation, interviews, and surveys. This research was expected to compete with competitors from other online-based mass media in terms of English news articles and vocational education and also useful for many parties, especially for TIMES Indonesia.